2019
DOI: 10.1039/c8nr10175b
|View full text |Cite
|
Sign up to set email alerts
|

Ion-induced assemblies of highly anisotropic nanoparticles are governed by ion–ion correlation and specific ion effects

Abstract: Ion-induced assemblies of highly anisotropic nanoparticles can be explained by a model consisting of ion–ion correlation and specific ion effects: dispersion interactions, metal–ligand complexes, and local acidic environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 52 publications
(105 citation statements)
references
References 40 publications
4
100
0
Order By: Relevance
“…This observation indicates that CNFs form stronger structures using CaCl 2 than NaCl, which is in accordance with previously reported studies. [58] For the sake of clarity, the aerogels will, from now on, be named according to following notation: "x:y z × 10 −3 m S", where x corresponds to the weight fraction of CNFs, y the weight fraction of alginate, z the added ionic strength, and S is the type of salt added; NaCl or CaCl 2 .…”
Section: Principles Of Aerogel Makingmentioning
confidence: 99%
“…This observation indicates that CNFs form stronger structures using CaCl 2 than NaCl, which is in accordance with previously reported studies. [58] For the sake of clarity, the aerogels will, from now on, be named according to following notation: "x:y z × 10 −3 m S", where x corresponds to the weight fraction of CNFs, y the weight fraction of alginate, z the added ionic strength, and S is the type of salt added; NaCl or CaCl 2 .…”
Section: Principles Of Aerogel Makingmentioning
confidence: 99%
“…This change in the dissociation, in turn, reduces the ionic swelling and increases the integrity of the material in water. This effect is visually observed in materials treated with Fe 3+ , since Fe 3+ complexes change color with pH and therefore act as an indirect measure of the pH of the local environment …”
Section: Introductionmentioning
confidence: 97%
“…In our previous work, we suggested that the attractive interaction in the presence of multivalent ions can essentially be explained by four different mechanisms. These mechanisms are illustrated in Figure and consist of a fundamental driving force from ion–ion correlation, which allows for the specific ion effects: dispersion interactions and metal–ligand complexes, in combination with a local acidic environment that changes the dissociation of the charged groups, to further “lock” the fibril network.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations